Effects of Dapagliflozin on Endothelial Dysfunction in Type 2 Diabetes Mellitus with Established Ischaemic Heart Disease (Edified) / Nur Aisyah Zainordin - Zainordin, Nur Aisyah (2017)
Background: SGLT-2 inhibitor has been shown to confer significant cardiovascular (CV) risk reduction in T2DM patients with ischaemic heart disease. However, the mechanism remains unclear. Endothelial dysfunction is a recognized independent predictor of cardiovascular events particularly in T2DM. It is effectively assessed via the measurements of flow-mediated vasodilatation (FMD). Aims: This study therefore aimed to demonstrate the effect of dapagliflozin on endothelial dysfunction as a possible mechanism in CV risk reductions in high-risk T2DM subjects. Methods: This was a prospective, double-blinds, placebo-controlled, clinical trial on T2DM patients with underlying ischaemic heart disease who were receiving metformin and insulin therapy (n=81). Subjects were randomised to receive 12-weeks therapy of either dapagliflozin (n=40) or placebo (n=41). Subjects underwent an endothelial function examination measured by AFMD and ANMD and surrogate markers; ICAM-1, eNOS, hsCRP and Lp(a) of according to the standard protocols. Glycaemic and lipid profiles were also measured as well as metabolic and hemodynamic changes. Results: After 12 weeks of therapy, dapagliflozin group demonstrated significantly bigger reductions of HbAlc and fasting blood sugar (FBS) compared to the placebo group (AHbAlc -0.16±1.25 vs. -0.83±1.47, p=0.042 and AFBS -1.90±4.40 vs -0.73±4.55, p=0.015, respectively). There is improvement in ICAM-1 level in dapagliflozin group which showed improvement in endothelial inflammation (AICAM-1, dapagliflozin group vs placebo group, -83.9± 205.9ng/mL : p<0.02 vs -11.0±169.1 ng/mL p= 0.699) . Albeit no statistical significance, there seemed to be a worsening of AFMD within the placebo group whilst the active group had similar values. Univariate correlation analysis revealed a significant negative correlation between HbAlc and AFMD within the active group (r= -0.31, p= 0.02) which was not seen within the placebo group. Conclusion: A 12-week therapy with dapagliflozin, in addition to insulin and metformin, resulted in significant reductions in HbAlc and FBS, which was further associated with improvement in endothelial dysfunction as measured by FMD and ICAM-1. Preservation of endothelial function within the dapagliflozin group could potentially attenuate progression of atherosclerosis in a group of patients with high plaque burden.